Antineoplastic Treatment and Renal Injury: An Update on Renal Pathology Due to Cytotoxic and Targeted Therapies. (September 2016) - Troxell, Megan L.; Higgins, John P.; Kambham, Neeraja
Abstract : Cancer patients experience kidney injury from multiple sources, including the tumor itself, diagnostic procedures, hypovolemia, infection, and drug exposure, superimposed upon baseline chronic damage. This review will focus on cytotoxic or targeted chemotherapy-associated renal injury. In this setting, tubulointerstitial injury and thrombotic microangiopathy (vascular injury) are more common than other forms of kidney injury including glomerular. Cisplatin, pemetrexed, and ifosfamide are well-known causes of acute tubular injury/necrosis. Acute interstitial nephritis seems underrecognized in this clinical setting. Interstitial nephritis is emerging as an "immune-related adverse effect" (irAE's) with immune checkpoint inhibitors in small numbers of patients. Acute kidney injury is rarely reported with targeted therapies such as BRAF inhibitors (vemurafinib, dabrafenib), ALK inhibitors (crizotinib), and mTOR inhibitors (everolimus, temsirolimus), but additional biopsy data are needed. Tyrosine kinase inhibitors and monoclonal antibodies that block the vascular endothelial growth factor pathway are most commonly associated with thrombotic microangiopathy. Other causes of thrombotic microangiopathy in the cancer patients include cytotoxic chemotherapies such as gemcitabine and mitomycin C, hematopoietic stem cell transplant, and cancer itself (usually high-stage adenocarcinoma with marrow and vascular invasion). Cancer patients are historically underbiopsied, but biopsy can reveal type, acuity, and chronicity of renal injury, and facilitate decisions concerning continuation of chemotherapy and/or initiation of renoprotective therapy. Biopsy may also reveal unrelated and unanticipated findings in need of treatment.